Simulation Assessment of Direct Push Injection Logging for High‐Resolution Aquifer Characterization. Issue 4 (25th September 2018) - Liu, Gaisheng; Borden, Robert C.; Butler, James J.
Abstract: Direct push injection logging (DPIL) has become one of the most widely used approaches for obtaining vertical profiles of hydraulic conductivity ( K ) in environmental site investigations. Despite its widespread use, however, there has been no rigorous analysis of the underlying physical processes that take place during DPIL or how the approach would perform under different hydrogeological and operating conditions. We address these issues through a series of numerical simulations. Results show that the ratio of DPIL injection rate over pressure can be used for direct determination of K when K is >10 −6 m/s. When K is <10 −6 m/s and specific storage (Ss) is >10 −3 /m, the ratio becomes increasingly sensitive to Ss; in that case, additional information on Ss is needed for reliable K estimation. For unconsolidated formations of moderate K or higher, the ratio of injection rate over pressure should provide a reasonable K estimate when Ss is <10 −3 /m. Although water injection at previous depths during continuous DPIL has only a small impact on the pressure response measured at the current injection depth, probe advancement can have a significant impact when K and Ss are small. Consequently, in fine‐grained materials, the advancement‐generated pore water pressure increase can comprise a large portion of the measured pressure response. To diminish the impact of probe advancement in such materials, advancement speed should be kept as low as possible (e.g., 0.5 cm/s). Abstract : Article impact statement : This work sheds light on direct push injection logging and provides valuable guidance on its use for environmental site investigation.